Efektivitas Pelaporan Akuntansi Realtime Berbasis Blockchain Untuk Perkembangan Bisnis - Mutia Halimatu S; Siti Nurhaliyah; Tita Rahmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Blockchain as a techonological tool that will change the way transactions in business and asset-based management are based. Simply put, blockchain is described as a series of records containing data managed by a group of computers in which there is no single entity, basically a blockchain like a digital ledger that can be accessed by anyone. The purpose of this study is to find out how the transformation of the development of accounting recording systems using blockchain technology is based on the results of analysis from literature studies. Literature study is a method of collecting data from various reference books and research results that have been referenced with the aim of obtaining a foundation for the problem being researched. The result of this research is how to transform traditional accounting into internet-based accounting using blockchain. This research provides implications regarding the application of blockchain to real-tine accounting reporting.